Festività e tradizioni religiose nella scuola plurale: alcune riflessioni a margine di una recente iniziativa legislativa - Ceffa, Claudia Bianca (Il diritto ecclesiastico, 2024)
Religious holidays and traditions in the plural school : some reflections on a recent legislative initiative · Embracing the cultural and identity value of Christian Catholic traditions and religious symbolism, bill n. 962, submitted on 11 December 2023 to the Senate, aims to prohibit in public educational institutions any action by school managers to prevent celebratory initiatives linked to the Christmas and Christian Easter holidays, including, for example, the setting up of the nativity scene. Regardless of the fate it will face at parliamentary level, this attempt at legislative regulation of religious pluralism within the school context represents an opportunity of certain interest not only for its more immediate constitutional implications, which lead to important questions in order to respect the secular and pluralist nature of the internal system but, also, to verify the nature of opportunity or, instead, of intrusion of such an initiative in the complex panorama of a society destined in the future to be increasingly less culturally homogeneous.